Extending DNA‐Based Molecular Photonic Wires with Homogeneous Förster Resonance Energy Transfer. Issue 3 (7th January 2016) - Díaz, Sebastián A.; Buckhout‐White, Susan; Ancona, Mario G.; Spillmann, Christopher M.; Goldman, Ellen R.; Melinger, Joseph S.; Medintz, Igor L.
Abstract : Molecular photonic wires (MPWs) precisely position dyes using structural DNA methodologies where they exploit Förster resonance energy transfer (FRET) to direct photonic energy over nm distances with potential applications in light harvesting, biosensing, and molecular electronics. Although versatile, the number of donor–acceptor dye pairs available and the downhill nature of FRET combine to limit the size and efficiency of current MPWs. HomoFRET between identical dyes should provide zero energy loss but at the cost of random transfer directionality. Here, it has been investigated what HomoFRET has to offer as a means to extend MPWs. Steady‐state‐, lifetime‐, and fluorescence anisotropy measurements along with mathematical models are utilized to experimentally examine various 3‐, 4‐, and 5‐dye MPW constructs containing from 1 to 6 HomoFRET repeat sections. Results show that HomoFRET can be extended up to 6 repeat dyes/5 steps with only a ≈55% energy transfer efficiency decrease while doubling the longest MPW length to a remarkable 30 nm. Critically, analogous constructs lacking the HomoFRET portion are unable to deliver any energy over the same lengths. Even with nondirectionality, the introduction of a repeated‐optimized HomoFRET transfer dye is preferable compared to additional less efficient dye species. HomoFRET further provides the benefit of having a higher energy output. Abstract : Molecular photonic wires (MPWs) position dyes using DNA and utilize Förster resonance energy transfer (FRET) to direct photonic energy. Available donor–acceptor dyes limit the size of current MPWs. HomoFRET between identical dyes should provide zero loss but with random directionality. Here, HomoFRET up to five steps in model constructs has been extended with only ≈50% energy transfer loss while doubling MPW length to 30 nm.